HLA‐A, B and DRB1 genetic heterogeneity in Quebec. (30th January 2015) - Buhler, S.; Nunes, J. M.; Sanchez‐Mazas, A.; Richard, L.
Summary Recent studies have shown that under specific conditions such as high sample sizes and Hardy–Weinberg equilibrium, bone marrow donor registry data can be used to describe HLA molecular variation across a specific geographic area, thus providing excellent data sets to infer human migrations history. The province of Quebec is known to have experienced a complex history of settlement, characterized by multiple migrations and demographic changes. We thus analysed the data of more than 13 000 unrelated individuals acting as volunteer bone marrow donors who were molecularly typed for HLA‐A, B and DRB1 polymorphisms in the Héma‐Quebec registry. HLA allelic and haplotypic frequencies were estimated and compared among regions. The results indicate that, despite an overall low genetic diversity in Quebec, genetic variation is correlated with geography, compatible with isolation‐by‐distance across the province. However, some localities also harbour contrasting genetic profiles, that is a highly diversified genetic pool in the two main urban centres (Montréal and Laval) and a more pronounced genetic divergence of two specific regions characterized by a peculiar peopling history (Saguenay‐Lac‐St‐Jean and Gaspésie‐Îles‐De‐La‐Madeleine). In agreement with other independent molecular markers, the observations based on HLA data thus account for the main demographic mechanisms that shaped the genetic structure of the present day Quebecer population. In addition, the detailed analysis of the Héma‐Quebec registry provides key genetic information on which an efficient bone marrow transplantation recruitment strategy can be settled.